The Importance of Activating and Building Knowledge - Stephanie Wessels (The Advocate, 2012)
Introduction: The following exchange occurred in a third-grade classroom: "I thought grit was a food. It doesn't make sense," Saida commented. "Yes, there are grits that people eat. Grits are ground corn, however, in this story the word is grit. Do you remember when it was really windy outside and dust and dirt got on you? That was grit," Mrs. Henning explained.